2020
DOI: 10.1089/jir.2020.0124
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effectiveness of Interferon-α2b Against COVID-19: The Cuban Experience

Abstract: A prospective observational study was conducted for assessing the therapeutic efficacy of interferon (IFN)-a2b in patients infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) during the first month after the coronavirus disease 2019 (COVID-19) outbreak began in Cuba. From March 11th to April 14th, 814 patients were confirmed SARS-CoV-2 positive in Cuba. Seven hundred sixty-one (93.4%) were treated with a combination of oral antivirals (lopinavir/ritonavir and chloroquine) with intramuscu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 16 publications
0
27
0
1
Order By: Relevance
“…A prospective observational study was conducted to assess the therapeutic efficacy of IFN-a2b in SARS-CoV-2 patients during the first month after the COVID-19 outbreak began in Cuba. Intramuscular administration of IFN-a2b improved both the rate of recovery and case fatalities (91). However, a retrospective cohort study demonstrated that there is great importance on the timing of administration of IFN-a2b with reduction of in-hospital mortality when administered the first five days of admission but increased mortality and delayed recovery was seen if given later (92).…”
Section: Canonical and Non-canonical Ifn Signaling In Antiviral Respomentioning
confidence: 99%
“…A prospective observational study was conducted to assess the therapeutic efficacy of IFN-a2b in SARS-CoV-2 patients during the first month after the COVID-19 outbreak began in Cuba. Intramuscular administration of IFN-a2b improved both the rate of recovery and case fatalities (91). However, a retrospective cohort study demonstrated that there is great importance on the timing of administration of IFN-a2b with reduction of in-hospital mortality when administered the first five days of admission but increased mortality and delayed recovery was seen if given later (92).…”
Section: Canonical and Non-canonical Ifn Signaling In Antiviral Respomentioning
confidence: 99%
“…The therapeutic Cuban protocol has included IFN-a (IFN alpha 2b, Heberon ALFA R, Cuba) therapy even though it is currently evaluated in clinical trials for COVID-19 patients (see at https:// rpcec.sld.cu/). The first results have been reported by Pereda et al (101), and although it was not a randomized clinical trial rather a retrospective analysis with a small control group of patients with no IFNa treatmentthe major outcomes were a reduction in time needed to obtain a negative qRT-PCR and more satisfactory recovery of treated patients. The abovementioned pieces of evidences suggest that type I IFN can be used both as, therapeutic as well as prophylactic agents against SARS-CoV-2.…”
Section: Type I Ifns: Preclinical and Clinical Studiesmentioning
confidence: 99%
“…Retrospective studies of COVID-19 patients treated with type I IFNs could help document the evidence of IFN effect in patients with and without comorbidities, specifically regarding easy-torecord clinical and laboratory parameters, all of which would support the wide range of IFNs effects beyond their antiviral and immunomodulatory roles. The shreds of evidence concerning the extensive therapeutic use of IFN-a in Cuba, as part of the national treatment guideline during the COVID-19 pandemic, demonstrate a significant reduction in the number of patients progressing to severe forms of COVID-19 (101).…”
Section: Ace2 Depletion Elicits Serious Pathological Events In Severementioning
confidence: 99%
“…In these trials, the efficacy of IFN was more marked when administered early during the disease course. In addition, investigators from Cuba also presented (pre-published) encouraging data on the use of IFN-α-2b by subcutaneous route in a prospective observational study, but this study contained several confounders which were not corrected by multivariable analysis (Pereda et al, 2020).…”
Section: Impact Of Type I Interferon Subcutaneous Injections On Covidmentioning
confidence: 99%